Competitive experience is associated with heart rate variability trends in collegiate sprint-swimmers during preparatory training - Ferrer, K.; Flatt, A. (The Journal of Strength and Conditioning Research, 2021)
Resting heart rate (RHR) and HR variability (HRV) are used as objective, physiological markers of training adaptation in swimmers. However, inter-individual differences in HRV patterns among swimmers, despite being exposed to the same training program, can be confusing to coaches. Therefore, further investigation into potential determinants of RHR and HRV is needed to facilitate interpretation of individual responses. Purpose: To quantify associations between years of competitive experience and cardiac-autonomic parameters among collegiate sprint-swimmers throughout preparatory training. Methods: Twenty-eight short-distance swimmers (17 males, 181 ± 10 cm, 78 ± 9 kg; 11 females, 178 ± 15 cm, 73 ± 12 kg) performed post-waking HRV measures (60 seconds) in the seated position with a validated mobile device throughout a 4-week preparatory phase. Weekly training consisted of 19.5 hours of total training time including 3, 60-minute resistance training sessions and 9, 90 to 120-minute pool sessions. The total planned volume load in swimming distance covered over the 4-week period was 136.6 km. The 4-week mean and coefficient of variation (CV, a marker of daily fluctuation) were calculated for RHR and the natural logarithm of the root mean square of successive differences (LnRMSSD, a parasympathetic HRV index). Years of competitive swimming experience was documented for each individual. Independent t-tests were used to compare RHR and LnRMSSD parameters between sexes. Pearson and partial correlations were used to quantify associations between variables. Results: Mean RHR (males vs. females, 64.4 ± 6.6 vs. 59.4 ± 6.6 b·min-1), LnRMSSD (4.2 ± 0.3 vs. 4.4 ± 0.4) and CV for RHR (10.1 ± 3.1 vs. 8.0 ± 2.3%) and LnRMSSD (7.2 ± 2.0 vs. 6.9 ± 3.3%) were not different between sexes (all p > 0.05). Associations were therefore quantified as one group (n = 28). Competitive experience (11.6 ± 4.1 years) was associated with mean LnRMSSD (r = 0.60, p < 0.001) and LnRMSSD CV (r = -0.52, p < 0.01), but not with mean RHR or RHR CV (p = 0.08-0.45). Accounting for multicollinearity between mean LnRMSSD and LnRMSSD CV (r = -0.55, p < 0.01), partial correlation analysis showed that competitive experience remained associated with mean LnRMSSD (r = 0.44, p = 0.02) but not LnRMSSD CV (r = -0.28, p = 0.15). Conclusions: Swimmers with a longer history of competitive experience maintained higher and more stable HRV throughout preparatory training. Practical Applications: Sprint-swimmers with a longer history of training and competing may exhibit higher and more stable HRV than less-experienced teammates, possibly due to higher aerobic fitness, or greater familiarity with the training stimulus. Minimal disturbance in autonomic activity throughout preparatory training may indicate that more experienced swimmers could tolerate greater training loads. Although whether more intensive training would offer a performance advantage remains to be determined.